Functional Outcomes of Basilar Thumb Arthritis Treatment with Tendon Suspension‐Interposition Arthroplasty: Retrospective Analysis with Mean Follow‐Up of 10 Years - Buruian, Alexei (2025)
Introduction: Thumb arthritis is a common condition. Its prevalence increases with age and predominantly affects females.   Methods: In the period from January 2009 to December 2014, 105 patients were submitted to trapezectomy, ligament reconstruction and tendon interposition for basilar thumb arthritis grades III and IV, of which 40 patients (42 hands) were included in the study. The majority, 92.5%, were females, with an average age of 59.6 ± 7.18 years, 52.5% were operated with an abductor pollicis longus tendon technique as described by Mathoulin and 47.5% with flexor carpi radialis tendon as described by Burton‐Pellegrini. The mean follow‐up time was 122.15 ± 25.3 months.   Results: The mean DASH score was 20.38±19.63, mean VAS score 2.3±302, Kapandji score 8.29±2.11, grip strength 19.5 ±10.91 kg, pulp pinch force 3.9±2.39 kg and lateral pinch force 4.77±2.33 kg. In terms of satisfaction 59.52% referred to maximum satisfaction with the surgery (5/5), 23.80% (4/5), 4.76% (3/5), 4.76% (2/5) and 7.14% minimum satisfaction (1/5). Analytically, males presented a greater grasp strength and lateral pinch and basilar thumb arthritis grade IV had worse outcomes. There are no significant differences in the results obtained with the different surgical techniques.   Conclusion: Trapezectomy and ligament reconstruction and tendon interposition present good medium‐long‐term func‐ tional results for the treatment of basilar thumb arthritis without statistically significant differences between Burton Pellegrini and Mathoulin techniques.